KEEFEKTIFAN PEMBELAJARAN AKUNTANSI MATERI JURNAL PENYESUAIAN DENGAN METODE COOPERATIVE SCRIPT DAN RESITASI - Resti Khanaliya; Kusmuriyanto (Economic Education Analysis Journal, 2017)
The purposes of this study are to (1) know the effectiveness of the teaching and learning of accounting subject in adjustment journal topic using cooperative script method. (2) know the effectiveness of the teaching and learning of accounting subject in adjustment journal topic using recitation method. (3) know which method that is more effective in teaching and learning of accounting subject in adjustment journal topic. This study used quasi experimental design with the design form of non equivalent control group design. The result of this study showed that cooperative script method is effective towards teaching and learning is 27,44% ; recitation method is effective towards teaching and learning is 50,47 %; which that the teaching and learning in the recitation method is more effective than the one cooperative script method.